Construction and initial validation of the International Trauma Questionnaire – Caregiver Version (ITQ-CG): assessing ICD-11 PTSD and CPTSD in children from caregiver perspective - Alexander Haselgruber; Dina Weindl-Wagner; Andrea Zagaria; Karin Zajec; Judith Noske; Brigitte Lueger-Schuster (European Journal of Psychotraumatology)
Objective: The 11th version of the International Classification of Diseases (ICD-11) introduces Posttraumatic Stress Disorder (PTSD) and complex PTSD (CPTSD) as two distinct trauma-related disorders. The International Trauma Questionnaire (ITQ) is the most widely used measure of assessment and has been adapted for use in children and adolescents (ITQ-CA), but a corresponding caregiver version is still missing. We aimed to close this gap by adapting the ITQ-CA and provide an initial validation of the ITQ – Caregiver Version (ITQ-CG). A corresponding measure of assessment from caregiver-perspective is integral for the use in child psychology, psychiatry and research.Method: Altogether, 326 children and adolescents who attended the department of child and adolescent psychiatry were rated by their caregivers using a set of standardized measures. Excluding patients due to missing data or no trauma exposure, a final sample of 223 patients was analysed. Factorial structure of the ITQ-CG and multiple forms of validity were examined using confirmatory factor, latent class and correlation analysis.Results: Confirmatory factor analysis supported the two-factor higher-order model of ICD-11 CPTSD as the factorial structure of the ITQ-CG. Convergent-divergent validity of main- and subscales of the ITQ-CG was evidenced by respective correlations with criterion variables. Latent class analysis supported the discriminant validity of the ITQ-CG, identifying a CPTSD-, PTSD-, DSO- and low symptoms-class. The CPTSD-class was associated with highest rates of comorbid psychopathology and functional impairment. Concurrent validity was evidenced by satisfactory concordance between caregiver- and child-reports.Conclusion: This study provides the construction and initial validation of the ITQ-CG to assess ICD-11 PTSD and CPTSD in children and adolescents from caregiver-perspective. We found compelling evidence for the ITQ-CGs validity, identifying it as an easy-to-use screening instrument to assess ICD-11 PTSD and CPTSD from caregiver-perspective. The ITQ-CG is freely available for clinicians and researchers.